Determination of a rational shape of a bulldozer blade considering the soil background of the Republic of Kazakhstan - N. T. Surashov; R. B. Asmatulaev; D. N. Tolymbek (Вестник СибАДИ, 2022)
Introduction. The productivity and efficiency of earth-cutting and transport machines (ETM) of the waste type depends on the nature and physical and mechanical properties of soils, i.e. on strength, connectivity, humidity, compactness, climatic conditions and on the region of the Republic of Kazakhstan. According to Professor R.A. Kabashev, the regions of Kazakhstan have mainly clay, sandy, loamy, sandy-gravel, coarse- and semi-rocky soils. Different designs and shapes of cutter blades, and therefore mouldboards, are required to develop these categories of soils to minimise cutting and digging resistance. Improved blade and blade designs result in higher productivity and energy efficiency, and the traction factor of the bulldozer is used effectively.When studying and analyzing literature sources, scientists of CIS and foreign countries came to the conclusion that the theory of interaction of working bodies of earth-moving machines with soils, typical for the middle belt of Russia and Ukraine, which are characterized by some connection between particles of II, III categories of soil strength, was reasonably created. Mechanisms of interaction of such soils with bulldozing equipment differ from the processes occurring when digging unbound and dense loamy soils typical for Kazakhstan.The material of this article represents the establishment of rational forms of the heap and the determination of optimum parameters of the heap depending on the category of the ground being mined, i.e., the creation of an adaptive working organ (WO) of the bulldozer, corresponding to its profile with natural trajectory of ground formation formation.Materials and methods. As materials, different categories of soils were used, widespread in the region of Kazakhstan and the new design of the bulldozer blade, equipped with a variety of sets of knives, i.e. ordinary straight knives - for planning work and the development of I-III categories of soils; with medium protruding knives (MPK) - for the development of dense IV-V categories or with stepped knives - for the development of hard, strong soils, etc. The process of their interaction with the maximum formation of the prism of drawing the soil before the blade, using the graphic-analytical method of research, was investigated.Outcomes. Studying the processes of interaction of WO and bulldozer knives with different categories of soils, rational designs of knives designed for the development of various categories of soils were established. The optimal parameters of the blade with the maximum set of the drawing prism before the blade are determined. Also, the blade is equipped with side knife extenders, upper visors and side bevels. The radius of curvature of the blade in the cross-section corresponds to the natural angle of chip formation of the soil layer, which allows to reduce the resistance of digging the soil.Discussion and conclusion. Until now, scientists of the CIS and foreign countries in the field of WO ETM of the waste type have studied in detail in theoretical terms and experimentally established promising designs of WO and bulldozer knives. Numerous methods for determining the parameters of the WO of the bulldozer depending on the category of the developed soil and taking into account the traction factor of the propulsion system, etc. However, they missed the study, with the maximum set of the prism of drawing the soil in front of the blade, its area of contact from the frontal surface of the blade and at the same time, adapted in the cross-section of the blade (radius of curvature of the blade) with the natural trajectory of chip formation of the soil layer.Taking into account these provisions, we have developed several options for the location of knives on the blade, taking into account the developed categories of soils:- a bulldozer blade with side bevels of the frontal surface for soft (sandy) soils;- bulldozer blade with MPK, side scarves and upper side bevels for strong, clay soils;- bulldozer blade with side bevels and side knives-extenders for loosened soils;- bulldozer blade with MPK, side scarves, side knives-extenders and upper bevels for densely strong soils (medium loam). For all these options (4 types of blade) blade design and knife location, it is recommended to determine the optimal parameters of the blade, taking into account the development of the soil category.